Festivals and the City: The Contested Geographies of Urban Events - Andrew Smith; Guy Osborn; Bernadette Quinn (University of Westminster Press, 2022)
This book explores how festivals and events affect urban places and public spaces, with a particular focus on their role in fostering inclusion. The 'festivalisation' of culture, politics and space in cities is often regarded as problematic, but this book examines the positive and negative ways that festivals affect cities by examining festive spaces as contested spaces. The book focuses on Western European cities, a particularly interesting context given the social and cultural pressures associated with high levels of in-migration and concerns over the commercialisation and privatisation of public spaces. The key themes of this book are the quest for more inclusive urban spaces and the contested geographies of festival spaces and places. Festivals are often used by municipal authorities to break down symbolic barriers that restrict who uses public spaces and what those spaces are used for. However, the rise of commercial festivals and ticketed events means that they are also responsible for imposing physical and financial obstacles that reduce the accessibility of city parks, streets and squares. Alongside addressing the contested effects of urban festivals on the character and inclusivity of public spaces, the book addresses more general themes including the role of festivals in culture-led regeneration. Several chapters analyse festivals and events as economic development tools, and the book also covers contested representations of festival cities and the ways related images and stories are used in place marketing. A range of cases from Western Europe are used to explore these issues, including chapters on some of the world's most significant and contested festival cities: Venice, Edinburgh, London and Barcelona. The book covers a wide range of festivals, including those dedicated to music and the arts, but also events celebrating particular histories, identities and pastimes. A series of fascinating cases are discussed - from the Venice Biennale and Dublin Festival of History, to Rotterdam's music festivals and craft beer festivals in Manchester. The diverse and innovative qualities of the book are also evident in the range of urban spaces covered: obvious examples of public spaces – such as parks, streets, squares and piazzas – are addressed, but the book includes chapters on enclosed public spaces (e.g., libraries) and urban blue spaces (waterways) too. This reflects the interpretation of public spaces as socio-material entities: they are produced informally through their use (including for festivals and events), as well as through their formal design and management.
Keywords: 320; Cities; Event management; Festivals; urban policy; Cultural heritage; tourism